Students' motivation for rubric use in the EFL classroom assessment environment - He, Chunxiu; Zeng, Jiayan; Chen, Jianlin (Frontiers in Psychology, 2022)
The effectiveness of a rubric depends on how it is enacted. Although students' efforts in rubric use vary, few studies have investigated the hidden motivations when rubrics are utilized for classroom assessment. This qualitative study attempts to categorize students' effort in rubric use and identify personal differences and contextual factors influencing the effort in the EFL classroom assessment environment. A total of 79 students at a Chinese university participated in the study. The data collected included their classroom oral presentation results and nine case study informants' retrospective interviews on their processes of rubric use. Focuses were drawn upon students' perceptions and practices of rubric use throughout the task process. Totally, three types of effort patterns emerged in light of students' self-ratings and descriptions of the use. The intense kind held firm trust in rubric utility and thus utilized the rubric to develop the targeted competence throughout the whole process. The medium type either selectively followed the rubric in optional phases of the process due to their judgments of the rubric and the task. The loose type was least responsive to the rubric since their actions seemed largely affected by their self-efficacy and prior experience. Results showed that students' effort in rubric use in classroom assessment was the outcome of cognitive appraisals of a rubric, students themselves, and a task. The study highlights trait motivation and task motivation in the effectiveness of rubric use in assessment practices. Implications on rubric employment and task design are drawn to tap students' motivation for rubric use to achieve assessment for learning.